1979
DOI: 10.1099/00221287-114-2-257
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids, Biological Properties and Efficacy of Nitrogen Fixation in Rhizobium japonicum Strains Indigenous to Alkaline Soils

Abstract: Plasmids were isolated from strains of Rhizobium japonicum, predominantly serogroup 135, obtained from soybean nodules collected at 15 sites in Nebraska, U.S.A. In addition to their serotype, these strains were indistinguishable from R. japonicum strain 311 b135 in growth rate, sensitivity to phage Rhj78 1, antibiotic sensitivities, general colony characteristics and rates of nitrogen fixation per plant. All strains occupied soil habitats with similar characteristics, including a high pH (7.2 to 8.3), relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Keyser et al (1984) examined the distribution of indigenous soybean-nodulating rhizobia in the United States and found that serogroup 123 was dominant in northern regions and B. elkanii in southern regions. Other studies support these results, with some exceptions in the case of alkaline soils, in which Bradyrhizobium serogroup 135 or Sinorhizobium/ Ensifer fredii predominate (Damirgi et al, 1967;Ham et al, 1971;Kowalski et al, 1974;Gross et al, 1979;Suzuki et al, 2008). Further studies are still needed, however, to examine the many environmental factors potentially affecting indigenous bradyrhizobia.…”
Section: Polar Ordination Of Community Diversity and Latitudesupporting
confidence: 53%
“…Keyser et al (1984) examined the distribution of indigenous soybean-nodulating rhizobia in the United States and found that serogroup 123 was dominant in northern regions and B. elkanii in southern regions. Other studies support these results, with some exceptions in the case of alkaline soils, in which Bradyrhizobium serogroup 135 or Sinorhizobium/ Ensifer fredii predominate (Damirgi et al, 1967;Ham et al, 1971;Kowalski et al, 1974;Gross et al, 1979;Suzuki et al, 2008). Further studies are still needed, however, to examine the many environmental factors potentially affecting indigenous bradyrhizobia.…”
Section: Polar Ordination Of Community Diversity and Latitudesupporting
confidence: 53%
“…While a few studies have reported the presence of two to four plasmids in B. japonicum strains, ranging in size from 74 to 294 kb (Gross et al, 1979;Masterson et al, 1982), the taxonomic status of some of the strains was not verified using molecular, phylogenetic tools (Gross et al, 1979;Masterson et al, 1982). Although Masterson et al (1982) showed that nod genes were not found on any plasmids they detected, no information was presented regarding the genetic composition of these plasmids, and thus the physiological role of plasmids in bradyrhizobia could not be inferred.…”
Section: Introductionmentioning
confidence: 99%
“…A biotype of Bradyrhizobium japonicum, indigenous to alkaline soils and competitive with commercial inoculants, was originally discovered in determining the cause of chlorosis in soybeans. The biotype ultimately was found to be highly efficacious in nitrogen fixation, despite slower growth than other strains of B. japonicum (4). Efforts to interest industry in commercializing these strains were unsuccessful owing to the limited potential market and the slow growth rate of the bacterium.…”
Section: Unanticipated Discoveries: Advances In Phytobacteriologymentioning
confidence: 99%